Modification of Baseball Beater for Elementary School Physical Education Learning (Journal of Physical Education and Sports, 2018)
The loss of interest and the decrease of students 'motivation towards the ball game is one of the students' difficulties in doing the punch because the batter has a very small cross-section, so the student's punch is rarely about the ball. Research using R & D development method. Procedures of development research conducted are: (1) potential and problem, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) Product Testing, (7) trial usage. The subjects of this research are the students of 5th grade of Elementary School. Instruments and techniques of data collection using questionnaires, field notes, and documentation. The conclusion of this research is (1) "Smart hitter" ball beater modification product can be used as medium of learning of game of soccer ball for elementary school, (2) modification product of ball beater "Smart hitters" can be used to improve the capability of basic motion techniques to hit the ball for the basics. (3) "Smart hitter" ball bearing modifiers can be used for playing ball games for elementary school.